2016
DOI: 10.4172/2161-1025.1000187
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Antibacterial and Antioxidative Property of Two Natural Honey Samples from Malda District, India

Abstract: Aims: The current study determines the antibacterial activity of 'Bakul' (Mimusops elengi) leaf, seed and bark extracts against gram-negative clinical bacterial isolates as well as the standard bacterial strains. Methods: The disc diffusion method was followed to determine the antibacterial activity of M. elengi leaf, seed and bark extracts against the clinical isolates of Escherichia coli, Klebsiella pneumoniae, Proteus vulgaris and Pseudomonas aeruginosa. The antibiotic susceptibility of the bacterial isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The study which was carried out to assess the antibacterial activity of honey from Ishielu Local Government Area of Ebonyi State on some pathogenic microorganisms (Staphylococcus aureus, Escherichia coli and Streptococcus pyogenes) isolated from wounds, confirmed the antibacterial efficacy of honey against the isolated bacterial species. The study also showed Staphylococcus aureus to be the most predominant bacterial species isolated from infected wounds, which is consistent with the study of Aynalem et al [20], Surajit et al [21] and Okeke et al [22]. However, this study varied with the report of Farrag et al [23] who reported Pseudomonas species as the most common isolates.…”
Section: Discussionsupporting
confidence: 91%
“…The study which was carried out to assess the antibacterial activity of honey from Ishielu Local Government Area of Ebonyi State on some pathogenic microorganisms (Staphylococcus aureus, Escherichia coli and Streptococcus pyogenes) isolated from wounds, confirmed the antibacterial efficacy of honey against the isolated bacterial species. The study also showed Staphylococcus aureus to be the most predominant bacterial species isolated from infected wounds, which is consistent with the study of Aynalem et al [20], Surajit et al [21] and Okeke et al [22]. However, this study varied with the report of Farrag et al [23] who reported Pseudomonas species as the most common isolates.…”
Section: Discussionsupporting
confidence: 91%
“…With its extraordinary features, such as the antibacterial, antioxidative and antiinflammatory effects [62,84], honey is currently used to enhance the silk fibroin-based biomaterials that are used in medical practice. There have been several silk fibroin honeyenhanced biomaterials developed, such as Manuka honey-enhanced silk fibroin matrices, silk fibroin cryogels that contain Manuka honey and honey-blended silk fibroin membranes [123,125].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the antibacterial activity, honey possesses another great characteristic when it comes to its biomedical applications, namely, it exhibits antioxidative effects [84]. The antioxidative effect has an important role by counteracting the action of oxidant compounds [85].…”
Section: Antioxidant and Anti-inflammatory Effectmentioning
confidence: 99%
“…This discrepancy in the antibacterial potency against selected pathogens could be ascribed to the chemistry of honey (its acidic pH 3.2-4.5, high osmolarity, hydrogen peroxide, non-peroxide factors), its phytochemical nature (content of phenols, tetracycline derivatives, amylase, streptomycin, sulfathiazole, fatty acids, ascorbic acid, flavonoides, trepens, benzyl alcohol and benzoic acids, etc. ), and geographic and seasonal (spatial and temporal) variation in honey collection (Mohapatra et al 2011;Tada et al 2012;Radhakrishnan et al 2014;Girotra et al 2016;Roy et al 2016). Further, there may exist a correlation between the microbial diversity and antibacterial potential of the hive bee's honey.…”
Section: Discussionmentioning
confidence: 99%